Method to Improve the Efficiency of the Traction Rolling Stock with Onboard Energy Storage - Yatsko, Sergii; Sidorenko, Anatolii; Vashchenko, Yaroslav; Liubarskyi, Borys; Yeritsyan, Bagish (My University, 2019)
This article presents the current problem of the introduction of onboard energy storages in electric transport. The energy diagrams of the electric transport operation have been analyzed, and the main stages of the rational selection of onboard energy storage capacity have been determined. A schematic of traction asynchronous electric drive system combined with onboard capacitive storage, with an improved energy storage module control system, has been provided. A simulation model of the underground rolling stock carriage in the Matlab/Simulink environment has been developed to confirm the proposed technical solution. The simulation modelling results demonstrate the more effective operation of the onboard storage control system at energy absorption, containment and recycling modes at rolling stock acceleration. The proposed algorithm of energy storage will reduce the cost of electricity for traction, reduce the power transfer and smooth the electricity consumption through an electric-traction network; it will improve traction and braking characteristics of the rolling stock.
Keywords: electric transport; onboard energy storage; simulation model; asynchronous electric drive; energy recovery